An experimental investigation into the combustion stability and emissions of an n-butanol/diesel blended fueled partially premixed compression ignition (PPCI) engine. (June 2023) - Kumar, Prem; Sandhu, Sarbjot Singh
Higher cyclic variability in internal combustion engines (ICE) increases driveability problems, specific fuel consumption, and exhaust emissions. Consequently, quantification of the combustion stability in different combustion parameters is essential for the design of closed-loop control for a partially premixed combustion (PPC). This research examines the impacts of a PPC strategy on the spectral features of IMEP combustion parameters for early, and late injection timings of a 4-cylinder CRDI engine using wavelet transforms (WT). Furthermore, operating points were optimized based on the combustion and emissions characteristics of the partially premixed compression ignition engine. Results indicated that the early start of injection (SOI) timing of 12° CA BTDC has a lower standard deviation in the time-series data of IMEP than the late SOI timing. Moreover, when the amount of n-butanol in diesel fuel was increased from 0% to 20% at a load of 2 bar BMEP, COVIMEP decreased from 3.1% to 2.75% at early SOI timing. The WT results reveal that the continuous strong intensity band pattern changes irregularly when the injection timing is advanced. It was also found that at lower cyclic variability conditions (SOI = 12°CA BTDC), CO and smoke emissions decreased, and there was a noticeable increase in NOx emissions.